Pengaruh Promosi Penjualan dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen pada UKM Home Industri Mie Wong Solo di Kabupaten Mamuju - Iwan Adinugroho; Andi Irfan; Abdullah (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of sales promotion and product quality on consumer purchasing decisions at Wong Solo Noodle Home Industry SMEs in Mamuju Regency, West Sulawesi. The method used in this research is quantitative method with descriptive-verification approach. Data were collected through distributing questionnaires to 30 respondents selected using purposive sampling. The data analysis technique used was multiple linear regression with the help of SPSS software. The results showed that sales promotion and product quality have a positive and significant effect on consumer purchasing decisions. This study provides recommendations for companies to improve promotional strategies and product quality to increase consumer loyalty.